2010
DOI: 10.1007/s12034-010-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate roughness on growth of diamond by hot filament CVD

Abstract: Polycrystalline diamond coatings are grown on Si (100) substrate by hot filament CVD technique. We investigate here the effect of substrate roughening on the substrate temperature and methane concentration required to maintain high quality, high growth rate and faceted morphology of the diamond coatings. It has been shown that as we increase the substrate roughness from 0⋅05 μm to 0⋅91 μm (centre line average or CLA) there is enhancement in deposited film quality (Raman peak intensity ratio of sp 3 to non-sp 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…CVD diamond grows between 700 ℃ and 1100 ℃ at sub-atmospheric pressure of 20-130 Torr; to deposit high-quality diamond with well-faceted morphology, the substrate temperature has to be on the higher side of 900 ℃, whereas substrate temperature lower than 700 ℃ produces cauliflower nanocrystalline morphology [31][32][33][34]. The growth rate initially increases with temperature, and after attaining maximum slowly decreases down.…”
Section: Introductionmentioning
confidence: 99%
“…CVD diamond grows between 700 ℃ and 1100 ℃ at sub-atmospheric pressure of 20-130 Torr; to deposit high-quality diamond with well-faceted morphology, the substrate temperature has to be on the higher side of 900 ℃, whereas substrate temperature lower than 700 ℃ produces cauliflower nanocrystalline morphology [31][32][33][34]. The growth rate initially increases with temperature, and after attaining maximum slowly decreases down.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the low roughness values achieved can be applied to create smoother interfaces for optical, tribological, thermal, and biomedical applications. The morphology differences between the growth on Si and stainless steel substrates can be due to the increased surface roughness of the stainless steel substrate. , It was found that increasing the substrate roughness leads to a more faceted growth, whereas smoother substrates produced a rounder, cauliflower-like morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology differences between the growth on Si and stainless steel substrates can be due to the increased surface roughness of the stainless steel substrate. 45,46 It was found that increasing the substrate roughness leads to a more faceted growth, whereas smoother substrates produced a rounder, cauliflower-like morphology. Finally, we demonstrate that the FVD system allows for facile addition of external electric fields to further control the growth of NCD films.…”
Section: Resultsmentioning
confidence: 99%
“…† Corresponding author: nagasaka.hiroshi@iri-tokyo.jp activation of gases is the first step in the diamond thinfilm growth. The growth of diamond films is dependent on many parameters [4][5][6][7][8][9][10], such as filament temperature, substrate temperature, substrate material, and reactant gas mixture.…”
Section: Introductionmentioning
confidence: 99%